Implementasai Pembelajaran Perilaku Pencegahan Penyalahgunaan Narkoba Dalam Pendidikan Jasmani - Brio Alfatihah; Tarpan Suparman; Aang Solahudin Anwar (LPPM Universitas Buana Perjungan Karawang, 2019)
Indonesia is a drug emergency, yes, this sentence illustrates the current condition of the Indonesian Replubic State. This is caused by rampant drug trafficking and abuse. In Indonesia, data from the National Narcotics Agency of the Republic of Indonesia shows in 2004 that 15% of Indonesia's population was involved in drug abuse (3.2 million) and in 2005 showed that 15,000 people died each year due to drugs (Jakarta Provincial Narcotics Agency, 2009) . The latest data on drug abuse in 2014 has increased by 4 million (BNN, 2015). Do not rule out the possibility of drug abuse will continue to increase in the following years as long as there is no education on the dangers of drug education at the Secondary School level Education is believed to solve the problem of the Indonesian people in order to avoid drug abuse. This belief is strengthened because education is a planned effort to influence others, whether individuals, groups, or the community, so that they do what is expected by education practitioners (Notoatmodjo, 2003: 16). In addition, in RI Law No. 20 of 2003 concerning the National Education System, article 1. Explains that: